PENGARUH PERGANTIAN AUDITOR, REPUTASI KAP DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY PADA PERUSAHAAN SUB SEKTOR BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nopi Anggraini; Nurmala, Nurmala; Emma Lilianti (Universitas Muhammadiyah Bengkulu, 2024)
This research aims to test the hypothesis of the influence of auditor change, company reputation and company size on audit delay. The population of this research is the coal subsector registered with BEI totaling 18 companies. The sampling technique was purposive sampling with 3 predetermined criteria. The are multiple linier regression analysis techniques, and normality test, multicollinearty test, autocorrelation test and heteroscedasticity test with the help of the SPPS version 24 program The result (R2) is 0.175 explained the variables change of auditor, KAP reputation and company size amounted to 17.5%, while 82,5% is explained by other variables not examined in this study. Hypotesis test result partially it shows that the significant value of changing auditors is 0,148 > 0,05 H1 is rejected and H0 is accepted which means there is no influence on audit delay, significant reputation of the company is 0.020 <0.05 H0 is rejected and H2 is accepted which means there is an influence on audit delay, and a significant value of company size is 0,051 < 0,05 h1 is accepted H0 is rejected which means there is no influence on audit delay0.012 < 0,05 H0 is rejected and H4 is accepted, concluding that simultaneously there is an influence of the variable change of auditor, reputation of the company and company size on audit delay. Meanwhile, in coal subsector companies registered in BEI for the 2018-2022. Keywords: Auditor Change, Hood Reputation, Company Size , Audit Delay